Embracing Diversity: Navigating Religious Identity in Multicultural Societies - Tobroni,; Bin Jamil, Asyraf Isyraqi; Eka Firmansyah, (Online Journal of Research in Islamic Studies, 2025)
This study aims to explore the experiences of minority religious groups in maintaining their religious identity within a multicultural society dominated by a majority religion. Through an extensive literature review, the author analyses key works that examine the complex dynamics between religious minorities and majorities. The study delves into the challenges faced by minority groups, including marginalization, discrimination, and the tension of identity negotiation, as they strive to preserve their distinct religious identity in the face of societal pressures to conform to the dominant culture. The research uncovers various strategies employed by these groups to navigate these challenges, such as building intra-community solidarity, engaging in interfaith dialogue, and advocating for greater religious tolerance and understanding. The findings of this research highlight the intricate nature of interreligious dynamics in heterogeneous societies and underscore the importance of fostering an environment of mutual respect, tolerance, and dialogue. By shedding light on the lived experiences of religious minorities, this study provides valuable insights into the mechanisms of religious identity preservation amidst external pressures. The practical implications of this research are significant, as it offers guidance for developing social intervention strategies aimed at promoting interreligious tolerance and cultivating a more inclusive, civic, and multicultural society. These strategies can serve as a foundation for policymakers, educators, and community leaders in their efforts to enhance religious harmony and social cohesion within diverse communities.